Involvement of Primary care in management of Schizophrenia in Low- and Middle-Income countries: Challenges and opportunities - Khan, Muhammad Firaz; Farooq, Saeed (Journal of Pakistan Psychiatric Society, 2021)
Schizophrenia is a chronic psychiatric disorder, which characteristically starts in early adulthood. It adversely affects the patient and family members, both emotionally and financially. Patients with this disorder have a significant decline in life expectancy, with potential 10-20 years of life lost. One most important aspect of the massive treatment gap and poor outcomes in people with Schizophrenia in low - and middle - income countries (LMICs) is slight or no involvement of General Practitioners (GPs) in its management. Essentially, Primary care physicians need training in aetiology, identification and treatment of this grave psychiatric illness, so they may provide better treatment to this group of patients